Strengthening Community Economic Independence through Home Industry-Based Virgin Coconut Oil (VCO) Production Training in Serang City - Abdur Rahman Irsyadi; Basrowi; Nani Rohaeni; Gema Ika Sari; Fahrurozi; Ela Melinda; Siti Hamdiah; Azmi Afifah; Silvia Maharani; Atik Budi Paryanti; Rahmadiana (Institut Teknologi dan Bisnis Asia Malang, 2026)
Purpose: This Community Service Program (PkM) aimed to strengthen community economic independence through home industry-based Virgin Coconut Oil (VCO) production training for unemployed community members in Serang City, Banten. The program addressed unemployment issues and the limited utilization of local resources for productive economic activities. Method: The program employed a participatory training approach involving lectures, demonstrations, hands-on practice, interactive discussions, and mentoring sessions. Training materials included coconut selection, VCO processing techniques, hygiene and quality control, packaging, and basic marketing strategies. The activity involved productive unemployed residents as the main participants. Practical Applications: The program provides practical benefits by equipping participants with entrepreneurial knowledge and technical skills that can be applied to establish sustainable home-based businesses, create additional income sources, and support local economic development. Conclusion: The program improved participants’ knowledge and practical skills in VCO production and increased motivation to develop independent businesses, contributing to community economic empowerment and unemployment reduction.